A Lexicostatistical Study: Language Kinship of Dayak Ngaju and Dayak Maanyan Language - Dilla Sintia; Imam Qalyubi; Misrita (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2025)
This study explores the linguistic kinship between the Dayak Ngaju and Dayak Maanyan languages, two prominent indigenous languages spoken in Central Kalimantan, Indonesia. Utilizing a lexicostatistical approach based on the 200-item Swadesh list vocabularies, the research aims to quantify the level of relatedness between the two languages and identify sound changes that mark their historical divergence. Data were collected through direct elicitation from native speakers and supplemented with secondary sources. The analysis found that 64 out of 200 vocabulary items are cognates, resulting in a kinship value of 32%, which classifies the relationship at the stock level. This indicates that while both languages likely share a common ancestral language, they have diverged significantly over time due to phonological shifts, socio-cultural factors, and geographic separation. Further comparative analysis revealed systematic sound changes. These findings contribute to a broader understanding of the Austronesian language family and emphasize the importance of preserving linguistic diversity in the Borneo region.